2019
DOI: 10.1108/md-04-2018-0478
|View full text |Cite
|
Sign up to set email alerts
|

A trasilient decision making tool for vendor selection: a hybrid-MCDM algorithm

Abstract: Purpose Vendor selection is the main activity in a sourcing decision, which is a strategic decision in that it leads enterprises to eliminate costs and improve their performance. However, an inappropriate selection may compromise the financial and operational status of the enterprise. But vendor selection is a complex, multi-criteria decision-making process because different and conflicting criteria have to be considered and assessed in order to find consistent suppliers. Consequently, evaluating and selecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…They take the advantage of each approach to develop the most accurate and suitable models. For instance, Mohammed et al (2018) utilized a hybrid DEMATEL-TOPSIS-ELECTRE based model to evaluate the overall suppliers' state on the basis of traditional business and resilience performance. Dobos and Vorosmarty (2014) used Data Envelopment Analysis (DEA) as a linear mathematical modelling technique to appraise the suppliers' environmental efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They take the advantage of each approach to develop the most accurate and suitable models. For instance, Mohammed et al (2018) utilized a hybrid DEMATEL-TOPSIS-ELECTRE based model to evaluate the overall suppliers' state on the basis of traditional business and resilience performance. Dobos and Vorosmarty (2014) used Data Envelopment Analysis (DEA) as a linear mathematical modelling technique to appraise the suppliers' environmental efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supplier evaluation and selection is one of the most challenging duties in supply chain management appreciating the truth that purchasing of raw materials and products may stand for 75% of a firm's initial capital costs (Mohammed et al, 2018). Hence, ineffective supplier selection may distress the firm's revenue.…”
Section: Introductionmentioning
confidence: 99%
“…Contractor selection process conventionally focused so much on the deliverables of the contractor. Mohammed, Harris, & Dukyil (2019), identified that traditional criteria (TC) for contractor selection are typical via performance based on cost and quality (please see Figure 1). That study proposed CS to also, take Resilience Criteria (RC) as a critical consideration.…”
Section: Financial Transparency In Contractor Selection Processmentioning
confidence: 99%
“…Traditionally, MCDM techniques have been popular in the financial sector (Ferreira et al , 2019). This research builds on recent works that applied TOPSIS to non-convectional MCDM problems, such as assessing and ranking the educational quality of free online instructional videos (Acuña-Soto et al , 2019), selecting the best vendor considering traditional and resilience criteria simultaneously (Mohammed et al , 2019), and integrating corporate social responsibility valuations with the financial performance of companies (Bilbao-Terol et al , 2019). Therefore, this study answers recent calls to alert practitioners and researchers to the practical applications of the MCDM approach (Ferreira et al , 2019) by creating a relevant tool to analyze the performance of TV programs and bringing lessons to the TV industry of how their products can be improved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, TOPSIS has been applied to examine the impact of perceived social media marketing activities on customer loyalty via customer equity drivers in an e-commerce context (Yadav et al , 2019), to optimize cryo-treated electrical discharge machining variables (Mohanty et al , 2018), to evaluate the performance of vendors to then select the best one (Mohammed et al , 2019), and the energy efficiency drivers in South Africa (Aye et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%